Status of benzimidazole resistance in intestinal nematode populations of livestock in Brazil: a systematic review. Issue 1 (December 2017) - Jaeger, Lauren; Carvalho-Costa, Filipe
Abstract Background Benzimidazoles (BZ) are a class of drugs widely used in veterinary and human medicine, creating a great selection pressure and the emergence of BZ resistance. We conducted a systematic review to assess the status of resistance and/or effectiveness reduction of BZ drugs in animal nematodes in Brazil, and make information accessible to the scientific community, as many studies are published in Portuguese. PubMed, SciELO Brasil, LILACS/Bireme, GNTD database, and Google Scholar were searched with no language restrictions. Results A total of 40 studies met our eligibility criteria (from the year 1989 forward). Sheep was the host most frequently analysed, and albendazole was the most frequently drug studied. The majority of studies (75.7%) showed that BZ drugs are insufficiently active (FECRT <80%) against nematode parasites of livestock. The mean FECRT for fenbendazole, thiabendazole, albendazole, mebendazole, oxfendazole, and ricobendazole were 71.8%, 71.8%, 58.6%, 53.9%, 46.9%, and 41.5%, respectively. It was observed through linear regression that FECRT is significantly reduced over time between 2007 and 2014 (R = −0.653p = 0.021) for the treatment of cattle with BZ, suggesting progressive loss of effectiveness and increased resistance for these hosts. Conclusions The scenario of BZ resistance in nematode populations in Brazil is not favourable. Given the high cost of drug discovery and development, it is urgent to implement control measures and to monitor the effectiveness/resistance to nematodes in livestock in Brazil.